Elevated mitochondrial DNA copy number in euthyroid individuals with impaired peripheral sensitivity to thyroid hormones - Qin, Li; Huang, Tingting; Zhang, Danmei; Li, Guochao; Wei, Liqin; Liu, Juan (Frontiers in Endocrinology, 2025)
BackgroundThe role of thyroid hormone sensitivity in metabolic and neoplastic diseases is well recognized, however, its association with mitochondrial DNA copy number (mtDNAcn) in euthyroid individuals remains unclear.ObjectiveThis cross-sectional study aimed to explore the relationship between thyroid hormone sensitivity and mtDNAcn in euthyroid individuals.MethodsWe recruited 350 hospitalized individuals with normal thyroid function between December 2020 and August 2022. Peripheral blood samples and clinical parameters were collected. Relative mtDNAcn levels were quantified by qPCR from peripheral blood samples. Peripheral thyroid hormone sensitivity was evaluated through the free triiodothyronine to free thyroxine (FT3/FT4) ratio, and central sensitivity was assessed using the thyrotrophic thyroxine resistance index (TT4RI), thyroid-stimulating hormone index (TSHI), and thyroid feedback quantile-based index (TFQI).ResultsSignificant differences in age and sex were observed between groups with lower and higher mtDNAcn. Multivariate linear regression analysis showed a negative correlation between mtDNAcn and the FT3/FT4 ratio after adjusting for confounders such as age, sex, BMI, alcohol consumption, smoking history, hypertension, diabetes, and hyperlipidemia. This negative correlation remained significant in subgroups of younger adults, females, normal-weight individuals, drinkers, non-smokers, and those with hypertension. No significant relationships were found between mtDNAcn and TSHI, TT4RI, or TFQI after adjusting for confounding factors.ConclusionReduced peripheral thyroid hormone sensitivity is linked to elevated mtDNAcn in euthyroid individuals, with variations based on age, sex, BMI, smoking, and hypertension.